Inaugural Health Equity and Actionable Disparities in Stroke: Understanding and Problem-Solving Symposium. Issue 11 (November 2020) - Towfighi, Amytis; Benson, Richard T.; Tagge, Raelle; Moy, Claudia S.; Wright, Clinton B.; Ovbiagele, Bruce
Abstract : Race/ethnic minorities face significant inequities in stroke incidence, prevalence, care, and outcomes. The Health Equity and Actionable Disparities in Stroke: Understanding and Problem-solving symposium, a collaborative initiative of the American Heart Association and National Institute of Neurological Disorders and Stroke, was the first-ever annual multidisciplinary scientific forum focused on race/ethnic inequities in cerebrovascular disease, with the overarching goal of reducing inequities in stroke and accelerating the translation of research findings to improve outcomes for race/ethnic minorities. The symposium featured esteemed invited plenary speakers, lecturing on determinants of race/ethnic inequities in stroke and interventions aimed at redressing the inequities. The Edgar J. Kenton III Award recognized Ralph Sacco, MD, MS, for his lifetime contributions to investigation, management, mentorship, and community service in the field of stroke inequities. Early career investigators were provided with travel awards to attend the symposium; presented their research at moderated poster and Think Tank sessions; received career development advice at the Building Momentum session; and networked with experienced stroke inequities researchers. Future conferences—The Health Equity and Actionable Disparities in Stroke: Understanding and Problem-solving 2021 to 2024—will broaden the focus to include 5 major persistent inequities (race/ethnic, sex, geographic, socioeconomic, and global). Each year will focus on a different theme (community and stakeholder engagement; clinical trials; implementation science; and policy and dissemination). By fostering a community of stroke inequities researchers, we hope to highlight promising work, illuminate research gaps, facilitate networking, inform policy makers, recognize achievement, inspire greater interest among junior investigators to pursue careers in this field, and provide networking opportunities for underrepresented minority scientists.